EFEK PEMBERIAN DAUN KELOR (Moringa Olifera Lam) TERHADAP PERTAMBAHAN BOBOT BADAN KAMBING BLIGON (Effect Of Moringa Leaves On The Body Weigth Bligon Does) - . Popalayah; M. Afa (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2017)
The objective of the research was to the Effect Moringa Leaves (Moringa Olifera Lam) On The Body Weight Bligon Does. This study uses eight bligon does females with age range of 3-3.5 years. Goats maintained intensively for 3 months, by feeding cattle adjusted to body weight. Feed given in the form of bran and forage (grasses and legumes) as much as 10% of their body weight and as feed additives given Moringa leaves as much 500 g/e/day. Water is supplied adlibitum. The weighing of cattle do as much 4 times that before the study (day 0), (30 days) (60 days) and (90 days). Variable observed in this study is to see how the effects of Moringa leaves on body weight gain and feed conversion bligon does feed with an additional form of Moringa leaves and were not given a smaller place. Analyzed descriptively difference between livestock demplot results by moringa leaves the moringa leaf is not given the unpaired t- test. The results of the research Moringa leaves as a feed supplement to cattle signifcant effect on the level of 0.05% of the body weight bligon does. Treatment with moringa leaves, relatively high average reached 23.8 kg / head, when compared to animals without giving moringa leaves only reached 8 kg / head. Feed conversion rasio on treatment ranges from 0.67 ± 0.94, while in cattle feed conversion rate without treatment ranges from 1.5 ± 1.7. The conclusion of this study is the use of Moringa leaves as feed supplement signifcantly affect weight gain bligon goat. The low feed conversion showed higher body weight gain.